Exporter Behavior, Country Size and Stage of Development : Evidence from the Exporter Dynamics Database - Fernandes, Ana M.; Freund, Caroline; Pierola, Martha Denisse (World Bank, Washington, DC, 2015)
This paper presents new data on the micro structure of the export sector for 45 countries and studies how exporter behavior varies with country size and stage of development. Larger countries and more developed countries have more exporters, larger exporters, and a greater share of exports controlled by the top 5 percent. The extensive margin (more firms) plays a greater role than the intensive margin (average size) in supporting exports of larger countries. In contrast, the intensive margin is relatively more important in explaining the exports of richer countries. Exporter entry and exit rates are higher and entrant survival is lower at an early stage of development. The paper discusses the results in light of trade theories with heterogeneous firms and the empirical literature on resource allocation, firm size, and development. An implication from the findings is that developing countries export less because the top of the firm-size distribution is truncated.